(3GdEQgGH hGSJQGJjLjI GdJYGed (B/s - (3YhGO, YeGOs ([(3GdbGgQI(B] :s (3OGQ GdfgVI GdYQHjI ;s, 2019)
(3jSYi gPG GdcJGH Edi Cf JTcd fhGI dOQGSGJ CNQi CcKQ JYebG ddXGgQI, agj dG JbJUQ abX Ydi JhXja GdEQgGH hdcf aj YQV UhQJjg ShGA eG jYQa HeUWdM (B%22(3EQgGH GdJfXjeGJ(B%22 (3Ch Pdc GdPj jJe JbOjeg Ydi Cfg (B%22(3EQgGH GdOhdI(B%22 (3hjfJbd GdcJGH HYO GSJYQGVg dCSHGH GfJTGQ GdXGgQI Edi WQM GdJMOj GdPj JeKdg ddYGde CLeY(B.s
(3HHdjhLQGajI (B: (3UaMI (B468-490.s
Keywords: (3GdJWQas; (3GdEQgGHs -- (3bhGfjf hJTQjYGJs; (3GdEQgGHs -- (3hbGjIs